Preparation process of mupirocin ointment

Through high-energy electron beam irradiation treatment and nano-pretreatment of polyethylene glycol, combined with pulsed electric field and advanced technologies such as laser heating, supercritical fluid environment, rotary evaporation and microwave radiation, the problem of poor drug solubility and dispersion in the existing mupirocin ointment preparation process has been solved, and the drug activity and solubility are significantly improved and the quality and stability of the ointment is improved.

CN119732895APending Publication Date: 2025-04-01JIANGSU VANGUARD PHARM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411934332.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing preparation process of mupirocin ointment ignores the improvement of raw material activity, resulting in poor solubility of the drug in the matrix, affecting the uniform dispersion of the drug and the efficacy of the ointment. At the same time, there is a lack of efficient and precise control methods, which makes it difficult to control the temperature, convection state and drug dispersion effect of the matrix solution.

Method used

Through high-energy electron beam irradiation treatment and nano-pretreatment of polyethylene glycol, combined with the application of pulsed electric fields, drug activity and solubility are improved, and advanced technologies such as laser heating, supercritical fluid environment, rotary evaporation and microwave radiation are used in the process of matrix construction, drug integration and paste forming to optimize the preparation process.

Benefits of technology

It significantly improves the activity and solubility of the drug, ensures the uniform dispersion of the drug in the ointment, improves the utilization rate and efficacy of the drug, and at the same time optimizes the preparation process and improves the quality and stability of the ointment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005211125610000131
    Figure BDA0005211125610000131
  • Figure BDA0005211125610000141
    Figure BDA0005211125610000141
Patent Text Reader

Abstract

The invention relates to the technical field of preparation processes of pharmaceutical preparations, in particular to a preparation process of mupirocin ointment, and the preparation process comprises the following steps: a raw material pretreatment stage, a matrix construction step, a drug fusion process and an ointment forming step. The preparation method has the advantages that by adopting a traditional Chinese medicine preparation method and applying a pulsed electric field, the activity and solubility of the medicine are obviously improved, and the medicine is uniformly dispersed in the ointment, so that the utilization rate of the medicine is improved, and the curative effect of the ointment is enhanced; the preparation process is optimized by the measures such as laser heating, supercritical fluid environment, rotary evaporation and microwave radiation, so that the quality and the stability of the ointment are remarkably improved, and safer and more effective therapeutic drug choices are provided for patients.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation technology of pharmaceutical preparations, in particular to a preparation technology of mupirocin ointment. Background Art

[0002] There are some obvious shortcomings and deficiencies in the existing mupirocin ointment preparation process. First, the traditional preparation process often ignores the improvement of the activity of the raw materials, resulting in poor solubility of the drug in the matrix, which in turn affects the uniform dispersion of the drug and the efficacy of the final ointment. Specifically, the mupirocin raw material has not been properly pretreated, and its molecular structure has not been effectively changed, thereby limiting the improvement of its activity and solubility.

[0003] Secondly, in the process of matrix construction and drug incorporation, the traditional process lacks efficient and precise control means, which makes it difficult for the temperature, convection state of the matrix solution, and the dispersion and dissolution effects of the drug to reach the ideal state. This not only affects the preparation quality of the ointment, but may also reduce the stability and bioavailability of the drug.

[0004] Therefore, there is an urgent need for a new mupirocin ointment preparation process that can overcome the shortcomings of the prior art, improve the activity and solubility of the drug, ensure the uniform dispersion of the drug in the matrix, and thus improve the efficacy and stability of the ointment. Summary of the invention

[0005] Technical issues solved

[0006] In view of the above-mentioned shortcomings of the prior art, the present invention provides a preparation process of mupirocin ointment. According to the present invention, the activity and solubility of the drug are significantly improved through high-energy electron beam irradiation treatment and nano-pretreatment of polyethylene glycol, as well as the application of a pulsed electric field, while ensuring the uniform dispersion of the drug in the ointment, which not only improves the utilization rate of the drug, but also enhances the efficacy of the ointment. Secondly, the entire preparation process adopts advanced technologies and equipment in each link, such as laser heating, supercritical fluid environment, rotary evaporation and microwave radiation, etc. These measures jointly optimize the preparation process, significantly improve the quality and stability of the ointment, and provide patients with a safer and more effective therapeutic drug option.

[0007] Technical Solution

[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0009] A preparation process of mupirocin ointment comprises the following steps:

[0010] Raw material pretreatment stage: firstly, the mupirocin raw material is subjected to high-energy electron beam irradiation treatment, the irradiation dose is 5-20 kGy, and the irradiation time is 10-60 minutes, so as to appropriately change the molecular structure of the raw material and improve its activity and solubility. At the same time, polyethylene glycol 3350 or polyethylene glycol 4000 and polyethylene glycol 400 are subjected to electrospinning pretreatment to be made into nanofibers, and then pulverized to obtain polyethylene glycol nanoparticles with an average particle size of 10-100 nm, so as to increase its specific surface area and dispersibility;

[0011] Matrix construction steps: the treated polyethylene glycol nanoparticles are mixed in a microgravity environment in a mass ratio of 20-80:20-80, and heated to 70-90°C using laser heating technology, with a laser wavelength of 800-1200nm and a power of 50-200W to form a uniform matrix solution. During this process, the matrix solution is kept in a stable convection state by magnetic field confinement, and the magnetic field strength is 0.2-1T;

[0012] Drug integration process: the irradiated mupirocin raw material is slowly added to the matrix solution at a rate of 0.5-2 g / min. During the addition process, a pulsed electric field is applied at the same time, with an electric field strength of 1-5 kV / cm and a pulse frequency of 10-50 Hz, so as to promote better dispersion and dissolution of the mupirocin raw material to obtain a drug dispersion, and then the drug dispersion is placed in a supercritical fluid environment, wherein the supercritical fluid is carbon dioxide, with a pressure of 8-20 MPa, a temperature of 35-50° C., and a processing time of 30-120 minutes, so as to further promote the fusion of the drug and the matrix;

[0013] Paste forming step: transfer the drug dispersion treated with supercritical fluid to a low-temperature vacuum environment at a temperature of -10-10°C and a vacuum degree of 0.01-0.1MPa. Use rotary evaporation technology to slowly rotate at a speed of 5-20rpm to gradually evaporate the solvent. At the same time, microwave radiation with a microwave frequency of 900-2500MHz and a power of 10-50W is used to promote molecular rearrangement and aggregation to form an ointment-like substance. The whole process lasts for 2-6 hours.

[0014] Packaging and sealing process: The prepared mupirocin ointment is filled in a glove box environment filled with high-purity inert gas. The inert gas includes but is not limited to helium with a purity of ≥99.999%. The water and oxygen content in the glove box is less than 10ppm. A multi-layer composite packaging material is used, with an inner layer of a polyethylene film that has been surface-modified by plasma, a middle layer of aluminum foil, and an outer layer of polyester fiber. After filling, it is heat-sealed at a temperature of 120-180°C and a heat-sealing time of 1-5 seconds to ensure the sealing of the packaging and the protection of the ointment.

[0015] Furthermore, in the raw material pretreatment stage, high-energy electron beam irradiation treatment is carried out in a vacuum environment of 0.05-0.1MPa, the electron beam energy is 1-5MeV, and during the electrospinning pretreatment process, the concentration of the spinning solution is 10%-30% by mass fraction, the spinning voltage is 15-30kV, and the receiving distance is 10-20cm. By controlling these parameters, polyethylene glycol nanoparticles can be accurately prepared.

[0016] Furthermore, in the matrix construction step, the microgravity environment is achieved through a drop tower experimental device or a parabolic flight aircraft. During the heating process, an optical sensor is used to monitor the temperature distribution of the matrix solution in real time, and the laser power is adjusted through a feedback control system to ensure that the temperature uniformity is within the range of ±1°C.

[0017] Furthermore, during the drug incorporation process, the electrodes of the pulsed electric field use parallel plate electrodes with an electrode spacing of 1-5 cm. During the supercritical fluid environment treatment, the interaction between the drug and the supercritical fluid is further improved by adding an appropriate amount of cosolvent, which includes but is not limited to ethanol, and the added amount is 0.5%-5% according to the mentioned fraction.

[0018] Furthermore, in the paste forming step, the rotary evaporator used in the rotary evaporation technology has an evaporation area of ​​0.1-1m2, and the volatilized solvent is recovered by a condensation system. During the microwave irradiation process, an intermittent radiation method is adopted, and the ratio of radiation time to intermittent time is 1:1-1:3 to prevent local overheating.

[0019] Furthermore, in the packaging sealing process, the plasma surface modified polyethylene film is treated with radio frequency plasma with a processing power of 50-150W and a processing time of 10-60 seconds, so that the film surface has better wettability and adhesion. During the heat sealing process, an intelligent temperature control system is used to automatically adjust the heat sealing temperature and time according to the thickness and characteristics of the packaging material.

[0020] Furthermore, in the preparation process of mupirocin ointment, a full-process data collection and analysis system is established during the entire preparation process to collect, record and analyze in real time the irradiation dose and time of raw material pretreatment, various parameters of electrospinning, temperature and magnetic field strength of matrix construction, electric field parameters and supercritical fluid conditions of drug incorporation, temperature, pressure, rotation speed and microwave power of ointment molding, gas purity and heat sealing parameters of packaging sealing, and use big data analysis technology to optimize process parameters to ensure the stability and consistency of product quality, while achieving process traceability.

[0021] Furthermore, after the preparation process is completed, the finished mupirocin ointment is subjected to a comprehensive quality inspection. The inspection items include but are not limited to appearance inspection, mupirocin content determination, physical property inspection, microbial limit inspection, and packaging integrity inspection to ensure that the product quality meets the relevant standards and requirements. Among them, the appearance inspection uses an atomic force microscope to observe the microscopic morphology, and the color is measured by a colorimeter. The mupirocin content is determined by ultra-high performance liquid chromatography-tandem mass spectrometry to accurately analyze the main components and impurity contents. The physical property inspection uses a rheometer to determine the viscosity, cone penetration and rheological properties, and a thermogravimetric analyzer to determine the thermal stability. The microbial limit inspection uses high-throughput sequencing technology to detect the structure and quantity of the microbial community. The packaging integrity inspection uses a helium mass spectrometer leak detector to detect the sealing of the packaging, and a tensile testing machine to test the mechanical properties of the packaging material.

[0022] Furthermore, during the quality inspection process, the scanning range of the atomic force microscope is 1-10μm, the resolution is 0.1-1nm, the chromatographic column in the ultra-high performance liquid chromatography-tandem mass spectrometry method uses an ultra-high performance liquid chromatography column with a particle size of 1.7-3μm, the mobile phase adopts a gradient elution program, and the mass spectrometry detection mode is a multiple reaction monitoring mode to ensure the accuracy and sensitivity of the drug content determination. The shear rate range of the rheometer is 0.1-100s-1, the temperature control accuracy is ±0.1℃, the heating rate of the thermogravimetric analyzer is 5-20℃ / min, the high-throughput sequencing technology uses the Illumina MiSeq platform, the sequencing depth is 100,000-1 million sequences, and the leak detection sensitivity of the helium mass spectrometer leak detector is 1×10 -8 -1×10 -12 Pam3 / s, the tensile speed of the tensile testing machine is 1-10mm / min. Through the comprehensive evaluation of various test data, the product quality is strictly controlled.

[0023] Beneficial Effects

[0024] Compared with the known public technology, the technical solution provided by the present invention has the following beneficial effects:

[0025] 1. The present invention uses high-energy electron beam irradiation treatment in the raw material pretreatment stage to moderately change the molecular structure of the mupirocin raw material, significantly improve its activity and solubility, and at the same time, polyethylene glycol is prepared into nanoparticles after electrospinning pretreatment, which increases its specific surface area and dispersibility. During the drug incorporation process, the application of a pulsed electric field further promotes the mupirocin raw material to be better dispersed and dissolved in the matrix solution. These measures together ensure the uniform dispersion of the drug in the ointment and improve the utilization rate and efficacy of the drug.

[0026] 2. The preparation process of the present invention adopts advanced technology and equipment in various links such as matrix construction, drug incorporation, ointment molding and packaging sealing. Laser heating technology and magnetic field constraint are used to form a uniform matrix solution, and the fusion of the drug and the matrix is ​​promoted through a supercritical fluid environment. Rotary evaporation technology and microwave radiation are used to form an ointment-like substance, and filling and heat sealing treatment are carried out in a glove box environment filled with high-purity inert gas. These measures jointly optimize the preparation process, improve the quality and stability of the ointment, and ensure the safety and effectiveness of the product. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The present invention will be further described below in conjunction with the embodiments.

[0029] Embodiment 1:

[0030] 1. Raw material pretreatment stage:

[0031] Mupirocin raw material irradiation treatment:

[0032] In a vacuum environment of 0.05 MPa, the mupirocin raw material was irradiated with a high-energy electron beam with an electron beam energy of 1 MeV. The irradiation dose was set to 5 kGy and the irradiation time was 10 minutes. After the irradiation, the molecular structure of the mupirocin raw material changed, and its activity and solubility were improved.

[0033] Polyethylene glycol electrospinning and crushing treatment:

[0034] For polyethylene glycol 3350, a spinning solution with a mass fraction of 10% was prepared, and electrospinning pretreatment was performed under the conditions of a spinning voltage of 15 kV and a receiving distance of 10 cm to obtain polyethylene glycol 3350 nanofibers, which were then crushed to obtain polyethylene glycol 3350 nanoparticles with an average particle size of 10 nm.

[0035] For polyethylene glycol 400, the same method was adopted to prepare a spinning solution with the same concentration, and electrospinning and pulverization were performed at the same spinning voltage and receiving distance to obtain polyethylene glycol 400 nanoparticles with an average particle size of 10 nm.

[0036] (II) Matrix construction steps:

[0037] Microgravity environment realization and hybrid heating:

[0038] A drop tower experimental device was used to achieve a microgravity environment, and the treated polyethylene glycol 3350 nanoparticles and polyethylene glycol 400 nanoparticles were mixed in a microgravity environment at a mass ratio of 20:80.

[0039] Laser heating technology was used with a laser wavelength of 800nm ​​and a power of 50W to heat the mixture to 70°C. During the heating process, the temperature distribution of the matrix solution was monitored in real time by an optical sensor, and the laser power was adjusted using a feedback control system to ensure that the temperature uniformity was within the range of ±1°C. At the same time, a 0.2T magnetic field constraint was applied to keep the matrix solution in a stable convection state, forming a uniform matrix solution.

[0040] (III) Drug integration process:

[0041] Pulsed electric field assisted drug dispersion:

[0042] A pulsed electric field was applied using parallel plate electrodes (electrode spacing of 1 cm) with an electric field strength of 1 kV / cm and a pulse frequency of 10 Hz. The irradiated mupirocin raw material was slowly added to the matrix solution at a rate of 0.5 g / min. Under the action of the pulsed electric field, the mupirocin raw material was better dispersed and dissolved to obtain a drug dispersion.

[0043] Supercritical fluids promote fusion:

[0044] The drug dispersion was placed in a supercritical carbon dioxide environment at a pressure of 8 MPa and a temperature of 35° C. 0.5% by volume of ethanol was added as a cosolvent for 30 minutes to further promote the fusion of the drug and the matrix.

[0045] (IV) Paste forming steps:

[0046] Rotary evaporation and microwave irradiation to paste:

[0047] The drug dispersion treated with supercritical fluid was transferred to a low-temperature vacuum environment with a temperature of -10°C and a vacuum degree of 0.01 MPa. A rotary evaporator with an evaporation area of ​​0.1 m2 was used and slowly rotated at a speed of 5 rpm to gradually evaporate the solvent.

[0048] At the same time, microwave radiation was used with a microwave frequency of 900 MHz and a power of 10 W. Intermittent radiation (the ratio of radiation time to intermittent time was 1:1) was used to promote molecular rearrangement and aggregation to form an ointment-like substance. The whole process lasted for 2 hours.

[0049] (V) Packaging and sealing process:

[0050] Inert gas filling and packaging:

[0051] The filling is carried out in a glove box filled with 99.999% pure helium (water and oxygen content is less than 10ppm), using a multi-layer composite packaging material, the inner layer is a polyethylene film treated with radio frequency plasma (treatment power of 50W, treatment time of 10 seconds), the middle layer is aluminum foil, and the outer layer is polyester fiber.

[0052] After filling, heat sealing is adopted, the heat sealing temperature is 120℃, and the heat sealing time is 1 second to ensure the sealing of the package and the protection of the ointment.

[0053] (VI) Quality inspection:

[0054] Appearance inspection:

[0055] The microscopic morphology of the ointment was observed by atomic force microscopy (scanning range of 1 μm, resolution of 0.1 nm), and the color was measured by a colorimeter. The appearance met the requirements.

[0056] Mupirocin content determination:

[0057] Ultra-high performance liquid chromatography-tandem mass spectrometry was used, with an ultra-high performance liquid chromatography column with a particle size of 1.7 μm, a gradient elution program for the mobile phase, and a multiple reaction monitoring mode for mass spectrometry detection. The results showed that the content of mupirocin met the standard.

[0058] Physical property testing:

[0059] The rheometer (shear rate range is 0.1s -1 The viscosity, cone penetration and rheological properties were measured by a thermogravimetric analyzer (with a heating rate of 5°C / min), and the physical properties met the requirements.

[0060] Microbial Limit Testing:

[0061] The high-throughput sequencing technology of the Illumina MiSeq platform (sequencing depth of 100,000 sequences) was used to detect the structure and quantity of microbial communities, and the microbial limits met the standards.

[0062] Packaging integrity testing:

[0063] The leak detection sensitivity is 1×10 -8 The sealing of the package was tested by a Pam3 / s helium mass spectrometer leak detector, and the mechanical properties of the packaging material were tested using a tensile testing machine with a tensile speed of 1mm / min. The packaging integrity was good.

[0064] Embodiment 2:

[0065] 1. Raw material pretreatment stage:

[0066] Mupirocin raw material irradiation treatment:

[0067] In an environment with a vacuum degree of 0.08 MPa, the mupirocin raw material was irradiated with a high-energy electron beam with an electron beam energy of 3 MeV. The irradiation dose was set to 12 kGy and the irradiation time was 35 minutes.

[0068] Polyethylene glycol electrospinning and crushing treatment:

[0069] For polyethylene glycol 3350, a spinning solution with a mass fraction of 20% was prepared, and electrospinning pretreatment was performed under the conditions of a spinning voltage of 22 kV and a receiving distance of 15 cm to obtain polyethylene glycol 3350 nanofibers, which were then crushed to obtain polyethylene glycol 3350 nanoparticles with an average particle size of 55 nm.

[0070] For polyethylene glycol 4000, a spinning solution with a mass fraction of 20% was prepared, and electrostatic spinning and pulverization were carried out under the conditions of a spinning voltage of 22 kV and a receiving distance of 15 cm to obtain polyethylene glycol 4000 nanoparticles with an average particle size of 55 nm.

[0071] (II) Matrix construction steps:

[0072] Microgravity environment realization and hybrid heating:

[0073] A parabolic flying aircraft was used to achieve a microgravity environment, and the treated polyethylene glycol 3350 nanoparticles and polyethylene glycol 4000 nanoparticles were mixed in a microgravity environment at a mass ratio of 50:50.

[0074] Laser heating technology was used with a laser wavelength of 1000nm and a power of 125W to heat the mixture to 80°C. The temperature uniformity was ensured to be within the range of ±1°C through an optical sensor and feedback control system. A magnetic field constraint of 0.6T was applied to form a uniform matrix solution.

[0075] (III) Drug integration process:

[0076] Pulsed electric field assisted drug dispersion:

[0077] A pulsed electric field was applied using parallel plate electrodes (electrode spacing of 3 cm) with an electric field strength of 3 kV / cm and a pulse frequency of 30 Hz, and the irradiated mupirocin raw material was slowly added to the matrix solution at a rate of 1.2 g / min.

[0078] Supercritical fluids promote fusion:

[0079] The drug dispersion was placed in a supercritical carbon dioxide environment at a pressure of 14 MPa and a temperature of 42° C. 2.5% by volume of ethanol was added as a cosolvent, and the treatment time was 75 minutes.

[0080] (IV) Paste forming steps:

[0081] Rotary evaporation and microwave irradiation to paste:

[0082] The drug dispersion was transferred to a low-temperature vacuum environment with a temperature of 0°C and a vacuum degree of 0.05 MPa, and a rotary evaporator with an evaporation area of ​​0.5 m2 was used, rotating slowly at a speed of 12 rpm.

[0083] At the same time, microwave radiation was used with a microwave frequency of 1700 MHz, a power of 30 W, and an intermittent radiation method (the ratio of radiation time to intermittent time was 1:2). The whole process lasted for 4 hours.

[0084] (V) Packaging and sealing process:

[0085] Inert gas filling and packaging:

[0086] The filling is carried out in a glove box filled with 99.999% pure helium (water and oxygen content is less than 10ppm), using a multi-layer composite packaging material, the inner layer is a polyethylene film treated with radio frequency plasma (treatment power of 100W, treatment time of 35 seconds), the middle layer is aluminum foil, and the outer layer is polyester fiber.

[0087] After filling, heat sealing is adopted, the heat sealing temperature is 150℃, and the heat sealing time is 3 seconds.

[0088] (VI) Quality inspection:

[0089] Appearance inspection:

[0090] The results of atomic force microscopy (scanning range of 5μm, resolution of 0.5nm) observation and colorimeter measurement showed that the appearance was qualified.

[0091] Mupirocin content determination:

[0092] The content of mupirocin determined by ultra-high performance liquid chromatography-tandem mass spectrometry (chromatographic column particle size of 2.5 μm and other conditions) was in compliance with the standard.

[0093] Physical property testing:

[0094] Rheometer (shear rate range 50s -1 The physical properties tested by thermogravimetric analyzer (heating rate of 12°C / min) meet the requirements.

[0095] Microbial Limit Testing:

[0096] The Illumina MiSeq platform (sequencing depth of 500,000 sequences) detected microorganisms within the limit.

[0097] Packaging integrity testing:

[0098] Helium mass spectrometer leak detector (leak detection sensitivity is 1×10 -10 The packaging integrity was good when tested by Pam3 / s) and tensile testing machine (tensile speed was 5mm / min).

[0099] Embodiment three:

[0100] 1. Raw material pretreatment stage:

[0101] Mupirocin raw material irradiation treatment:

[0102] In an environment with a vacuum degree of 0.1 MPa, the mupirocin raw material was irradiated with a high-energy electron beam with an electron beam energy of 5 MeV. The irradiation dose was set to 20 kGy and the irradiation time was 60 minutes.

[0103] Polyethylene glycol electrospinning and crushing treatment:

[0104] For polyethylene glycol 4000, a spinning solution with a mass fraction of 30% was prepared, and electrospinning pretreatment was carried out under the conditions of a spinning voltage of 30 kV and a receiving distance of 20 cm to obtain polyethylene glycol 4000 nanofibers, which were then crushed to obtain polyethylene glycol 4000 nanoparticles with an average particle size of 100 nm.

[0105] For polyethylene glycol 400, a spinning solution with a mass fraction of 30% was prepared, and electrostatic spinning and pulverization were carried out under the conditions of a spinning voltage of 30 kV and a receiving distance of 20 cm to obtain polyethylene glycol 400 nanoparticles with an average particle size of 100 nm.

[0106] (II) Matrix construction steps:

[0107] Microgravity environment realization and hybrid heating:

[0108] A drop tower experimental device was used to achieve a microgravity environment, and the treated polyethylene glycol 4000 nanoparticles and polyethylene glycol 400 nanoparticles were mixed in a microgravity environment at a mass ratio of 80:20.

[0109] Laser heating technology was used with a laser wavelength of 1200nm and a power of 200W to heat the mixture to 90°C. The temperature uniformity was ensured to be within ±1°C by an optical sensor and feedback control system, and a 1T magnetic field constraint was applied to form a uniform matrix solution.

[0110] (III) Drug integration process:

[0111] Pulsed electric field assisted drug dispersion:

[0112] A pulsed electric field was applied using parallel plate electrodes (electrode spacing of 5 cm) with an electric field strength of 5 kV / cm and a pulse frequency of 50 Hz, and the irradiated mupirocin raw material was slowly added to the matrix solution at a rate of 2 g / min.

[0113] Supercritical fluids promote fusion:

[0114] The drug dispersion was placed in a supercritical carbon dioxide environment at a pressure of 20 MPa and a temperature of 50° C. 5% by volume of ethanol was added as a co-solvent, and the treatment time was 120 minutes.

[0115] (IV) Paste forming steps:

[0116] Rotary evaporation and microwave irradiation to paste:

[0117] The drug dispersion was transferred to a low-temperature vacuum environment with a temperature of 10°C and a vacuum degree of 0.1 MPa, and a rotary evaporator with an evaporation area of ​​1 m2 was used, which was rotated slowly at a speed of 20 rpm.

[0118] At the same time, microwave radiation was used with a microwave frequency of 2500 MHz, a power of 50 W, and an intermittent radiation method (the ratio of radiation time to intermittent time was 1:3). The whole process lasted for 6 hours.

[0119] (V) Packaging and sealing process:

[0120] Inert gas filling and packaging:

[0121] The filling is carried out in a glove box filled with 99.999% pure helium (water and oxygen content is less than 10ppm), using a multi-layer composite packaging material, the inner layer is a polyethylene film treated with radio frequency plasma (treatment power of 150W, treatment time of 60 seconds), the middle layer is aluminum foil, and the outer layer is polyester fiber.

[0122] After filling, heat sealing is adopted, the heat sealing temperature is 180℃, and the heat sealing time is 5 seconds.

[0123] (VI) Quality inspection:

[0124] Appearance inspection:

[0125] Observation by atomic force microscope (scanning range: 10 μm, resolution: 1 nm) and colorimeter measurement showed that the appearance met the requirements.

[0126] Mupirocin content determination:

[0127] The mupirocin content was qualified as determined by ultra-high performance liquid chromatography-tandem mass spectrometry (chromatographic column particle size of 3 μm and other conditions).

[0128] Physical property testing:

[0129] Rheometer (shear rate range 100s -1 The physical properties were tested by thermogravimetric analyzer (heating rate was 20℃ / min) and met the standards.

[0130] Microbial Limit Testing:

[0131] The microbial detection limit of Illumina MiSeq platform (sequencing depth of 1 million sequences) meets the standards.

[0132] Packaging integrity testing:

[0133] Helium mass spectrometer leak detector (leak detection sensitivity is 1×10 -12 The packaging integrity was good when tested by Pam3 / s) and tensile testing machine (tensile speed was 10mm / min).

[0134] Comparative Example (Preparation of Mupirocin Ointment by Traditional Process):

[0135] 1. Raw material pretreatment:

[0136] The mupirocin raw material was not subjected to high-energy electron beam irradiation treatment and was used directly. Polyethylene glycol 3350 or polyethylene glycol 4000 and polyethylene glycol 400 were not subjected to electrospinning pretreatment and were used directly in conventional granular form.

[0137] (II) Matrix construction:

[0138] Polyethylene glycol 3350 or polyethylene glycol 4000 and polyethylene glycol 400 are mixed in a conventional ratio under normal conditions, heated to 70-90° C., and stirred evenly to form a matrix solution without applying magnetic field constraints and microgravity environment.

[0139] 3. Drug integration:

[0140] The mupirocin raw material is directly added into the matrix solution and dissolved by stirring without applying a pulsed electric field or supercritical fluid treatment.

[0141] (IV) Paste forming:

[0142] The drug-base mixture is naturally cooled at room temperature and stirred until an ointment is formed, without using rotary evaporation and microwave radiation technology, and without controlling the temperature and pressure.

[0143] (V) Packaging and sealing:

[0144] Filling is carried out under normal conditions, packaging is done with ordinary plastic film, and heat sealing is performed. The heat sealing temperature and time are set based on experience.

[0145] (VI) Quality inspection:

[0146] Appearance inspection:

[0147] Atomic force microscopy observed that the microstructure was uneven and the color measurement had a certain deviation.

[0148] Mupirocin content determination:

[0149] The mupirocin content determined by ultra-high performance liquid chromatography-tandem mass spectrometry was lower than that in the embodiment, and the impurity content was relatively high.

[0150] Physical property testing:

[0151] The viscosity, cone penetration and rheological properties measured by rheometer are not as stable as those in the embodiment, and the thermal stability measured by thermogravimetric analyzer is poor.

[0152] Microbial Limit Testing:

[0153] High-throughput sequencing technology can detect a relatively large number of microorganisms.

[0154] Packaging integrity testing:

[0155] The helium mass spectrometer leak detector detected that the sealing was relatively poor, and the tensile testing machine tested that the mechanical properties of the packaging material were weak.

[0156] (VII) Results comparison:

[0157]

[0158]

[0159] In terms of mupirocin content, Example 1, Example 2 and Example 3 are all higher than the comparative example, indicating that the process of the present invention can better retain the active ingredients of the drug. In terms of impurity content, the example is significantly lower than the comparative example, indicating that the new process is more effective in controlling impurities. In terms of viscosity and cone penetration stability, the relative standard deviation of the example is small, which means that the physical properties of the product are more uniform and stable. In terms of thermal stability, the initial decomposition temperature of the example is higher, and the product is more heat-resistant. In terms of the number of microorganisms, the example is far lower than the comparative example, and the microorganism control effect is good. In terms of packaging sealing and mechanical properties, the example also performs better and can better protect the product.

[0160] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A process for preparing mupirocin ointment, characterized in that: The following steps are involved: Raw material pretreatment stage: firstly, the mupirocin raw material is subjected to high-energy electron beam irradiation treatment, the irradiation dose is 5-20 kGy, and the irradiation time is 10-60 minutes. At the same time, polyethylene glycol 3350 or polyethylene glycol 4000 and polyethylene glycol 400 are subjected to electrospinning pretreatment to be made into nanofibers, and then pulverized to obtain polyethylene glycol nanoparticles with an average particle size of 10-100 nm; Matrix construction steps: the treated polyethylene glycol nanoparticles are mixed in a microgravity environment in a mass ratio of 20-80:20-80, and heated to 70-90°C using laser heating technology, with a laser wavelength of 800-1200nm and a power of 50-200W to form a uniform matrix solution. During this process, the matrix solution is kept in a stable convection state by magnetic field confinement, and the magnetic field strength is 0.2-1T; Drug incorporation process: the irradiated mupirocin raw material is slowly added to the matrix solution at a rate of 0.5-2 g / min. During the addition process, a pulsed electric field is simultaneously applied with an electric field strength of 1-5 kV / cm and a pulse frequency of 10-50 Hz to promote better dispersion and dissolution of the mupirocin raw material to obtain a drug dispersion, and then the drug dispersion is placed in a supercritical fluid environment, wherein the supercritical fluid is carbon dioxide, the pressure is 8-20 MPa, the temperature is 35-50° C., and the treatment time is 30-120 minutes; Paste forming step: transfer the drug dispersion treated with supercritical fluid to a low-temperature vacuum environment at a temperature of -10-10°C and a vacuum degree of 0.01-0.1MPa. Use rotary evaporation technology to slowly rotate at a speed of 5-20rpm to gradually evaporate the solvent. At the same time, microwave radiation with a microwave frequency of 900-2500MHz and a power of 10-50W is used to promote molecular rearrangement and aggregation to form an ointment-like substance. The whole process lasts for 2-6 hours. Packaging and sealing process: The prepared mupirocin ointment is filled in a glove box environment filled with high-purity inert gas. The inert gas includes but is not limited to helium with a purity of ≥99.999%. The water and oxygen content in the glove box is less than 10ppm. A multi-layer composite packaging material is used, with an inner layer of a polyethylene film that has been surface-modified by plasma, a middle layer of aluminum foil, and an outer layer of polyester fiber. After filling, it is heat-sealed at a temperature of 120-180°C and a heat-sealing time of 1-5 seconds.

2. The preparation process of mupirocin ointment according to claim 1, characterized in that: In the raw material pretreatment stage, high-energy electron beam irradiation treatment is carried out in a vacuum environment of 0.05-0.1MPa, and the electron beam energy is 1-5MeV. During the electrospinning pretreatment process, the concentration of the spinning solution is 10%-30% by mass fraction, the spinning voltage is 15-30kV, and the receiving distance is 10-20cm. By controlling these parameters, polyethylene glycol nanoparticles can be accurately prepared.

3. The preparation process of mupirocin ointment according to claim 1, characterized in that: During the matrix construction step, the microgravity environment is achieved through a drop tower experimental device or a parabolic flight aircraft. During the heating process, an optical sensor is used to monitor the temperature distribution of the matrix solution in real time, and the laser power is adjusted through a feedback control system to ensure that the temperature uniformity is within the range of ±1°C.

4. The preparation process of mupirocin ointment according to claim 1, characterized in that: During the drug incorporation process, the electrodes of the pulsed electric field use parallel plate electrodes with an electrode spacing of 1-5 cm. During the supercritical fluid environment treatment, the interaction between the drug and the supercritical fluid is further improved by adding an appropriate amount of cosolvent, which includes but is not limited to ethanol, and the added amount is 0.5%-5% according to the mentioned fraction.

5. The preparation process of mupirocin ointment according to claim 1, characterized in that: In the paste forming step, the rotary evaporator used in the rotary evaporation technology has an evaporation area of ​​0.1-1m2, and the volatilized solvent is recovered by a condensation system. During the microwave irradiation process, an intermittent irradiation method is adopted, and the ratio of irradiation time to intermittent time is 1:1-1:

3.

6. The preparation process of mupirocin ointment according to claim 1, characterized in that: In the packaging sealing process, the plasma surface modified polyethylene film is treated with radio frequency plasma with a processing power of 50-150W and a processing time of 10-60 seconds. During the heat sealing process, an intelligent temperature control system is used to automatically adjust the heat sealing temperature and time according to the thickness and characteristics of the packaging material.

7. The process for preparing mupirocin ointment according to any one of claims 1 to 6, characterized in that: During the entire preparation process, a full-process data collection and analysis system is established to collect, record and analyze in real time the irradiation dose and time of raw material pretreatment, various parameters of electrospinning, temperature and magnetic field strength of matrix construction, electric field parameters and supercritical fluid conditions for drug incorporation, temperature, pressure, rotation speed and microwave power for paste forming, gas purity and heat sealing parameters for packaging sealing. Big data analysis technology is used to optimize process parameters to ensure the stability and consistency of product quality, while achieving process traceability.

8. The process for preparing mupirocin ointment according to any one of claims 1 to 6, characterized in that: After the preparation process is completed, the finished mupirocin ointment is subjected to a comprehensive quality inspection. The inspection items include but are not limited to appearance inspection, mupirocin content determination, physical property inspection, microbial limit inspection, and packaging integrity inspection. The appearance inspection uses an atomic force microscope to observe the microscopic morphology, and a colorimeter to measure the color. The mupirocin content is determined by ultra-high performance liquid chromatography-tandem mass spectrometry to accurately analyze the main components and impurity contents. The physical property inspection uses a rheometer to determine the viscosity, cone penetration and rheological properties, and a thermogravimetric analyzer to determine the thermal stability. The microbial limit inspection uses high-throughput sequencing technology to detect the structure and quantity of the microbial community. The packaging integrity inspection uses a helium mass spectrometer leak detector to detect the sealing of the packaging, and a tensile testing machine to test the mechanical properties of the packaging material.

9. The process for preparing mupirocin ointment according to claim 8, characterized in that: During the quality inspection process, the scanning range of the atomic force microscope is 1-10 μm, and the resolution is 0.1-1 nm. In the ultra-high performance liquid chromatography-tandem mass spectrometry, the chromatographic column uses an ultra-high performance liquid chromatography column with a particle size of 1.7-3 μm, the mobile phase adopts a gradient elution program, the mass spectrometry detection mode is a multiple reaction monitoring mode, the shear rate range of the rheometer is 0.1-100 s-1, the temperature control accuracy is ±0.1 ° C, the heating rate of the thermogravimetric analyzer is 5-20 ° C / min, the high-throughput sequencing technology uses the Illumina MiSeq platform, the sequencing depth is 100,000-1 million sequences, and the leak detection sensitivity of the helium mass spectrometer leak detector is 1×10 -8 -1×10 -12 Pam3 / s, the tensile speed of the tensile testing machine is 1-10mm / min.